Studi Hasil Tes Kebugaran Jasmani Siswa Kelas Atas di Sekolah Dasar Negeri 03 Talang Tulungagung Tahun Ajaran 2019 - Putra Aprilian Trisnata; Yulingga Nanda Hanief; Ruruh Andayani Bekti (Jurnal Literasi Olahraga, 2020)
This research is motivated by the lack of data about the physical fitness of students at SDN 03 Talang Tulungagung. This study aims to determine the level of physical fitness of upper-class students at SDN 03 Talang Tulungagung. This research is a descriptive study using a survey method with data collection techniques using a test that is the Indonesian Physical Fitness Test (TKJI). Subjects in this study were upper-class students at SDN 03 Talang Tulungagung, totaling 56 children consisting of 25 male students and 31 female students. Data analysis techniques using descriptive analysis as outlined in the form of a percentage of physical fitness level, which is divided into 5 categories, namely: lack of once, less, enough, good, and very good based on the TKJI classification. The results obtained physical fitness level of upper-class students at SDN 03 Talang Tulungagung, namely 0 children (0%) with a very good category, 9 children (16.07%) with a good category, 43 children (76.79%) with enough categories, 4 participants (7.14%) with fewer categories, and 0 participants (0%) with fewer categories. The highest frequency is in the medium category, which is 43 children (76.79%). Thus the level of physical fitness of upper-class students at SDN 03 Talang Tulungagung is included in the sufficient category.